Temozolomide analogs with improved brain/plasma ratios – Exploring the possibility of enhancing the therapeutic index of temozolomide. Issue 20 (15th October 2016) - Rai, Roopa; Banerjee, Monali; Wong, Darren H.; McCullagh, Emma; Gupta, Ashu; Tripathi, Shailendra; Riquelme, Eduardo; Jangir, Ramnivas; Yadav, Shyamraj; Raja, Mohd.; Melkani, Pankaj; Dixit, Vikas; et al.
Graphical abstract: Abstract: Temozolomide is a chemotherapeutic agent that is used in the treatment of glioblastoma and other malignant gliomas. It acts through DNA alkylation, but treatment is limited by its systemic toxicity and neutralization of DNA alkylation by upregulation of the O 6 -methylguanine-DNA methyltransferase gene. Both of these limiting factors can be addressed by achieving higher concentrations of TMZ in the brain. Our research has led to the discovery of new analogs of temozolomide with improved brain:plasma ratios when dosed in vivo in rats. These compounds are imidazotetrazine analogs, expected to act through the same mechanism as temozolomide. With reduced systemic exposure, these new agents have the potential to improve efficacy and therapeutic index in the treatment of glioblastoma.